Supervising theses: congruence between the expectations of supervisors and supervisees / Habibah Ashari and Md. Rizal Md. Yunus - Ashari, Habibah; Md. Yunus, Md. Rizal (ACRULeT, Faculty of Education & UiTM Press, 2006)
Supervising theses at doctoral and master’s level is never easy. Complaints are often heard from both sides. Supervisors lament the fact that their students do not have the relevant skills to carry out research; students complain that supervisors are very difficult to contact and do not seem to provide much assistance. More often than not, supervisees expect the supervisors to guide them through every detail and aspect of the research writing process. The findings revealed that supervisors and supervisees have different conceptions of their roles and have different expectations of each other. The findings suggest that both parties need to clarify their expectations from the outset. This may minimize conflicts between the two parties.